Complete Genome Sequence of Escherichia coli Phage Paul - Holt, Ashley (Microbiol Resour Announc, 2019)
Escherichia coli is both a commensal and a pathogen in humans and other animals. Here, we describe the isolation of E. coli strain 4s bacteriophage Paul. The complete 79,429-bp genome was annotated and demonstrates similarity with phieco32viruses, as does its prolate podophage morphology.